Improving the Mechanism of Financial Management of Investment Projects (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, conclusions and proposals were formed on the issues of financing investment activities, creating a favorable investment environment, factors affecting investment activities, analysis of the activities of enterprises with participation of foreign investments and their improvement.